2011
DOI: 10.5127/jep.019211
|View full text |Cite
|
Sign up to set email alerts
|

Biased Self-Perception of Social Skills in Anxious Children: The Role of State Anxiety

Abstract: The role of state and trait anxiety on observer ratings of social skill and negatively biased self-perception of social skill was examined. Participants were aged between 7 and 13 years (M = 9.65; SD = 1.77; N = 102), 47 had a current anxiety diagnosis and 55 were non-anxious controls. Participants were randomly allocated to a high or low anxiety condition and asked to complete social tasks. Task instructions were adjusted across conditions to manipulate participants' state anxiety. Observers rated anxious par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The SST was used to get an indication of the children’s levels of anxiety during an anxiety-provoking situation. As the literature is inconclusive as to whether socially anxious individuals behave differently from non-anxious individuals during anxiety-provoking situations [ 22 ], we decided to measure self-reported anxiety [see also 26 ]. The child was asked to indicate anxiety on a 0- to 10-point Likert scale ranging from “not anxious at all” to “very anxious”, right before the instructions of the SST, when the child was relaxed and unaware of having to perform the SST.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SST was used to get an indication of the children’s levels of anxiety during an anxiety-provoking situation. As the literature is inconclusive as to whether socially anxious individuals behave differently from non-anxious individuals during anxiety-provoking situations [ 22 ], we decided to measure self-reported anxiety [see also 26 ]. The child was asked to indicate anxiety on a 0- to 10-point Likert scale ranging from “not anxious at all” to “very anxious”, right before the instructions of the SST, when the child was relaxed and unaware of having to perform the SST.…”
Section: Methodsmentioning
confidence: 99%
“…For spider fear, we applied a Behavior Avoidance Task (BAT) related to spiders, as previous studies have shown that spider fearful children find it very difficult to approach spiders [ 25 ]. For social anxiety, we included a Social Speech Task (SST), based on studies showing that socially anxious children find it very distressing to be the center of attention and to be evaluated on their social performance [ 22 , 26 ]. The aim of the current study was to add both the BAT and SST to the self-reports, and to examine the relationship between interpretation bias and both behavioral measures and self-reported fear and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…“Kids are going to laugh at me”; Schniering and Rapee 2004). Social threat thoughts were measured with five items of the social threat scale of this questionnaire, supplied by Dodd et al (2011) together with their social speech protocol: “I’m worried that I’m going to get teased; I’m going to look silly; People are thinking bad things about me; I look like an idiot; I’m afraid I will make a fool of myself”. The items are scored on a five-point scale from 0 ( not at all ) to 4 ( all the time ).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure of the two minute speech task was similar to the protocol of the high anxiety condition used by Dodd et al (2011). All children performed the task individually in a separate room at school, together with a trained research assistant.…”
Section: Methodsmentioning
confidence: 99%
“…When it comes to social communication deficits, there is some evidence for both self and observer rated social communication deficits in groups of children with both mixed anxiety disorders (e.g. Dodd et al, 2011 ) and social anxiety disorder specifically ( Spence et al, 1999 ) compared to non-anxious children. However, others have only found evidence for deficits according to self-, but not observer-ratings (e.g.…”
Section: Introductionmentioning
confidence: 99%